Residential care in California: Spatial and temporal trends in facility development and care capacity. (28th September 2021) - Frochen, Stephen; Ailshire, Jennifer; Rodnyansky, Seva; Sheehan, Connor
Abstract : The development of residential care has not kept pace with the growth of the older population in many places. We merged the California Department of Social Services residential care for the elderly dataset with census place data to document the growth of facilities and beds per older adults in all of California and in its three largest cities. From 1996 to 2015, residential care steadily increased in California by the number of facilities and beds relative to older adults. However, due to a consistently increasing older adult population, the Cities of San Diego and San Jose experienced gradual and intermittent decline in capacity per older adults, respectively, even as they added many beds to their inventories from the sporadic development of large assisted living and continuing care retirement communities. Additionally, San Jose and Los Angeles exhibited the most overlap in densities of facility development and oldest old adults, with San Diego showing less intersection in cartographic analyses. Understanding facility development and care capacity trends can help local agencies and jurisdictions in the United States and other countries discern whether planning policies and other geographical and development factors appropriately encourage the development of residential care and other long‐term care facilities . Key Messages: Residential care and other forms of long‐term care are increasing along with the older adult population, but not uniformly across space and time. In certain locations, residential care capacity as measured in beds per older adults has decreased or experienced intermittent growth and decline. The greatest densities of oldest old adults in the jurisdictions studied appear to have overlapped with at least small traces of the residential care industry in cartographic analyses. Abstract : Les centres de soins pour personnes âgées en Californie: les tendances spatiales et temporelles dans la mise en place d'infrastructures: L'implantation de centres de soins en Californie n'a pas suivi le rythme de la croissance de la population âgée dans de nombreux secteurs. Afin d'étudier ce phénomène, nous avons combiné l'ensemble des données sur ce sujet provenant du California Department of Social Services et du recensement américain afin de documenter la croissance des installations et des lits par adultes âgés à l'échelle de la Californie et, plus précisément, dans ses trois plus grandes villes. De 1996 à 2015, les centres de soins pour personnes âgées ont régulièrement augmenté en Californie en termes de nombre d'établissements et de lits. Toutefois, en raison d'une augmentation constante de la population plus âgée, les villes de San Diego et de San Jose ont connu un déclin relatif de leur capacité d'accueil, même si elles ont ajouté de nombreux lits à leurs inventaires par le biais du développement de grands villages de retraite. Sur le plan géographique, San Jose et Los Angeles ont présenté de nombreux chevauchements de densités d'installations et de personnes âgées alors que San Diego montrait une meilleure couverture territoriale de l'offre de services. La compréhension des tendances dans la localisation des centres de soin et dans les capacités d'offrir des soins peut aider les organismes locaux et les États à déterminer si planification des services est appropriée en matière de construction d'établissements et d'autres installations de soins de longue durée .